A combination of four active compounds alleviates cerebral ischemia–reperfusion injury in correlation with inhibition of autophagy and modulation of AMPK/mTOR and JNK pathways. Issue 10 (7th May 2014) - Guo, Zhongshun; Cao, Guosheng; Yang, Haopeng; Zhou, Huana; Li, Long; Cao, Zhengyu; Yu, Boyang; Kou, Junping
<x xml:space="preserve">Abstract</x> SMXZF is a combination of Rb1, Rg1, schizandrin, and DT‐13 (6:9:5:4) derived from Sheng‐mai San, a widely used Chinese traditional medicine for the treatment of cardiovascular and cerebral diseases. The present study explores the inhibitory effects and signaling pathways of SMXZF on autophagy induced by cerebral ischemia–reperfusion injury. Male C57BL/6 mice were subjected to ischemia–reperfusion insult by right middle cerebral artery occlusion (MCAO) for 1 hr with subsequent 24 hr reperfusion. Three doses of SMXZF (4.5, 9, and 18 mg/kg) were administered intraperitoneally (i.p.) after ischemia for 1 hr. An autophagic inhibitor, 3‐methyladenine (3‐MA; 300 μg/kg), was administered i.p. 20 min before ischemia as a positive drug. We found that SMXZF significantly increased cerebral blood flow and reduced the infarct volume, brain water content, and the neurological deficits in a dose‐dependent manner. Similar to the positive control, SMXZF at 18 mg/kg also significantly inhibited autophagosome formation. Immunofluorescence staining and Western blotting demonstrated that SMXZF could significantly decrease the expression levels of beclin1 and microtubule‐associated protein 1 light chain 3. SMXZF also remarkably inhibited the phosphorylation of adenosine monophosphate‐activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) as well as the expression of c‐Jun N‐terminal kinase (JNK) and its phosphorylation induced by 24 hr reperfusion. Finally, we demonstrated that the optimal administration time of SMXZF was at the early period of reperfusion. This study reveals that SMXZF displays neuroprotective effect against focal ischemia–reperfusion injury, possibly associated with autophagy inactivation through AMPK/mTOR and JNK pathways. © 2014 Wiley Periodicals, Inc.